ASSOCIATION OF FUSOBACTERIUM NUCLEATUM WITH HALITOSIS - Ireh Choe (International Educational Journal of Science and Engineering, 2024)
This paper focuses on 3 main negative effects of Fusobacterium nucleatum on halitosis. Halitosis, which is known as bad breath, is a common disease among people. Fusobacterium nucleatum produces VSCs, such as hydrogen sulfide and methyl mercaptan, which cause halitosis. Another effect of Fusobacterium nucleatum is that it triggers periodontal disease to induce halitosis. The microbe also collaborates with other bacteria like Porphyromonas gingivalis and Capnocytophaga ochracea to leave a negative influence on bad breath. It is important to recognize this issue in order to further examine and create future treatments.